2024
DOI: 10.1039/d3sc06734c
|View full text |Cite
|
Sign up to set email alerts
|

A scalable synthesis of adjuvanting antigen depots based on metal–organic frameworks

Ryanne N. Ehrman,
Olivia R. Brohlin,
Yalini H. Wijesundara
et al.

Abstract: ZIF-8 vaccine enhances the humoral immune response through sustained antigen exposure to the immune system whilst zinc adjuvants the vaccine via inducing T cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…154 It is important to understand, however, that the FDA-approved adjuvant alum is more cytotoxic than ZIF-8 and that the same approximate dose used to vaccinate mice would be used in humans, which are comparatively gigantic. 227 The material needed is typically only 10−50 μg of antigen, meaning the MOF needed is typically well below a milligram. Further, vaccines are not injected into the blood, and most of their degradation occurs at the injection site.…”
Section: Limitations and Unrealized Advantages Of Using Reticular Pla...mentioning
confidence: 99%
See 1 more Smart Citation
“…154 It is important to understand, however, that the FDA-approved adjuvant alum is more cytotoxic than ZIF-8 and that the same approximate dose used to vaccinate mice would be used in humans, which are comparatively gigantic. 227 The material needed is typically only 10−50 μg of antigen, meaning the MOF needed is typically well below a milligram. Further, vaccines are not injected into the blood, and most of their degradation occurs at the injection site.…”
Section: Limitations and Unrealized Advantages Of Using Reticular Pla...mentioning
confidence: 99%
“…This toxicity is aided by the ability of MOFs to escape the endo/lysosome, which enables cytosolic delivery of their metals . It is important to understand, however, that the FDA-approved adjuvant alum is more cytotoxic than ZIF-8 and that the same approximate dose used to vaccinate mice would be used in humans, which are comparatively gigantic . The material needed is typically only 10–50 μg of antigen, meaning the MOF needed is typically well below a milligram.…”
Section: Limitations and Unrealized Advantages Of Using Reticular Pla...mentioning
confidence: 99%
“…Compared to other template materials, MOFs have been considered as ideal templates based on their high specific surface areas and high porosity . Particularly, zeolitic imidazolate framework (ZIF-8), composed of zinc ions and 2-methylimidazolate, exhibited excellent advantages as template material in nanoparticle fabrication due to the high loading capability, mild removal condition and pH-responsive dissociation. Works from our lab and others showed that using ZIF-8 NPs as templates to prepare nanoparticles could achieve effective loading of payloads and intracellular delivery. Additionally, poly­(ethylene glycol) (PEG) could act as a mineralizer to improve the dispersity, stability, and cargo loading capacities of ZIF-8 NPs. …”
Section: Introductionmentioning
confidence: 99%
“…46 The presence of zinc in ZIF-8 has recently been shown to traffic to the lymph node and increase T-cell activation and cytokine production. 47 Further, Zn 2+ has implications in the activation of cGAS; Zn 2+ is necessary for the enzyme to produce the CDN cGAMP after the detection of DNA. 48 MOFs-the ZIF family in particular-can be tuned through reticular synthesis, allowing for the modular incorporation of multiple different linkers 49 or multiple metals 50 to create multivariate MOFs with properties unique or distinct from MOFs made of a single metal or ligand.…”
Section: Introductionmentioning
confidence: 99%